Sosialisasi pentingnya social distancing dan mencegah pola hidup dalam upaya memutus rantai penyebaran covid-19 - Maria Herlinda Dos Santos; Hasnah Hasnah; Umrah Bahar (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
Covid-19 is one of the outbreaks whose spread is very significant in human life today, almost all circles discuss and anticipate this outbreak in various ways, some are washing their hands all the time using soap, some are cleaning their hands by using a hand sanitizer, some even do sports and maintain their diet so that their immunity is maintained during this pandemic. Given that Covid-19 is transmitted through physical contact and regardless of age and sex. Therefore, apart from exercising and adjusting our diet, we are also obliged to have adequate rest. In this community service activity aimed at Karang Taruna to participate in the socialization of